Composición química del ensilaje de pasto elefante (Pennisetum purpureum Schum) con diferentes niveles de inclusión de cáscaras de maracuyá (Passiflora edulis) - Ganchozo Bravo, Jenniffer Scarleth (2019)
The objective of this research was to evaluate the chemical composition of elephant grass silage with different inclusion levels of passion fruit peel (10, 20, 30 and 40%). The inclusion of passion fruit peel in the silage of elephant grass (100, 90, 80, 70 and 60%) was done to obtain the composition of dry matter, organic matter, inorganic matter, crude protein, neutral detergent fiber and acid detergent fiber. A completely randomized design was applied with five treatments and five repetitions. The data obtained were analyzed by means of a free software statistical program. The differences between treatment means were checked with the Tukey test (p≤0.05). The analysis of variance showed that the percentage of passion fruit does not affect all of its simple nutrients from the treatments (T1 = 100PE, T2 = 90PE + 10CM, T3 = 80PE + 20CM, T4 = 70PE + 30CM and T5 = 60PE + 40CM), they were similar in MS, NDF and FDA and different in MO, Ashes, PB, and EE. The 10, 20 and 30% inclusion of passion fruit reached higher values (p <0.05) for MO (85.32, 85.54 and 84.57% in order). The treatments with inclusion of passion fruit peel obtained 5.63% (T2); 5.25% (T3); 5.58% (T4), and 5.98% (T5), presenting the best protein proportions (p <0.05) compared to the control. The EE content had its highest peak in the T2 treatment (90% PE + 10% CM) with 1.43%, decreasing it as the inclusion of passion fruit peel increases to the elephant grass silage with 1.18% (T3); 0.92% (T4) and 0.9% (T5). The inorganic waste was different between them, thus the treatments T1 (18.27%), T4 (15.43%) and T5 (17.98%) showed higher contents (p <0.05) at T2 (14.68%) and T3 (14.46%). It is appreciated that T1 (100% PE) and T5 (60% PE and 40% CM) could contribute with more mineral availability. The contents of FDN and FDA show a quadratic trend, the inclusion levels of passion fruit peel have their highest concentration of NDF in the treatment T1 (100% PE) with 79.19%. However, with the mixture of 10% CM (76.65%), 20% CM (76.81%) and 30% CM (74.98%) in the elephant grass silage the NDF percentages were reduced, but tended to increase in T5 (60% PE + 40% CM) with 75.52%. The FDA concentrations showed a similar tendency to the NDF. Keywords: Pennisetum purpureum, passion fruit peel, silage, microsilos, chemical composition